2019
DOI: 10.32615/ps.2019.070
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic response of cabbage in cadmium-spiked soil

Abstract: Efficiency of a photosynthetic apparatus in plants growing in cadmium-spiked soil as well as plant biomass and cadmium accumulation were assessed in two cabbage cultivars (early and late) in a long-term pot experiment. Cadmium concentrations were 10 and 40 mg(Cd) per kg of dry mass of soil. The early cultivar showed a dose-dependent and stable decrease in SPAD index, while in plants of the late cultivar the response was reversible and less pronounced. A huge drop in the effective quantum yield of PSII photoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…In the current study, Cd-stressed rice plants displayed phenotypic changes, including decreased growth, leaf rolling, burning of leaf tips, chlorosis, and yellowing of the entire plant (Figure 1A), suggesting that the presence of excessive Cd can induce toxicity effects on hydroponically grown rice plants. The decrease in biomass of Cd-stressed rice plants (Figure 1B) was also detected in other plant species (e.g., wheat, mustard, Brassica oleracea, and Pisum sativum ) exposed to various levels of Cd for short or long periods [13,31,32,33]. In contrast, addition of exogenous salicylic acid (SA) and/or sodium nitroprusside (SNP) to growth medium was found to mitigate Cd-induced phytotoxic effects by restoring plant growth and biomass (Figure 1B), reviving green color, reducing leaf rolling, and improving the overall phenotypic appearance (Figure 1A).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the current study, Cd-stressed rice plants displayed phenotypic changes, including decreased growth, leaf rolling, burning of leaf tips, chlorosis, and yellowing of the entire plant (Figure 1A), suggesting that the presence of excessive Cd can induce toxicity effects on hydroponically grown rice plants. The decrease in biomass of Cd-stressed rice plants (Figure 1B) was also detected in other plant species (e.g., wheat, mustard, Brassica oleracea, and Pisum sativum ) exposed to various levels of Cd for short or long periods [13,31,32,33]. In contrast, addition of exogenous salicylic acid (SA) and/or sodium nitroprusside (SNP) to growth medium was found to mitigate Cd-induced phytotoxic effects by restoring plant growth and biomass (Figure 1B), reviving green color, reducing leaf rolling, and improving the overall phenotypic appearance (Figure 1A).…”
Section: Discussionmentioning
confidence: 62%
“…Instead, Cd is accumulated in plant tissues through the transporters that are involved in the uptake of other essential elements like magnesium, calcium, manganese, iron, and zinc [30]. Once accumulated at excessive concentrations, Cd shows toxic effects by disturbing metabolism of plants, resulting in growth inhibition and biomass reduction [3,31]. In the current study, Cd-stressed rice plants displayed phenotypic changes, including decreased growth, leaf rolling, burning of leaf tips, chlorosis, and yellowing of the entire plant (Figure 1A), suggesting that the presence of excessive Cd can induce toxicity effects on hydroponically grown rice plants.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional method of reducing the toxicity by replacing the soil contaminated with heavy metals is highly expensive, and the placement of contaminated soil might become an urgent problem to be solved, which could even cause secondary pollution [5]. At present, phytoremediation has become a more promising method of environmental restoration based on biological extraction and filtration [6][7][8][9]. Hyperaccumulators have good application prospects in the remediation of contaminated soil, such as the first known arsenic (As) hyperaccumulation plant Pteris vittata [10][11][12], the manganese (Mn) hyperaccumulation plant Phytolacca acinosa [13,14], Sedum [15,16] with super enrichment ability to Cd, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Plant photosynthesis is affected by diverse environmental factors such as Cd [10,27], salinity, and drought [28], leading to reduced crop yields. For example, Gao et al [26] showed that Cd concentration significantly inhibited plant growth and photosynthesis in rice.…”
Section: Introductionmentioning
confidence: 99%